Russian Federation Financial Sector Assessment Program : Anti-Money Laundering and Combating the Financing of Terrorism - International Monetary Fund (Washington, DC, 2017)
This technical note (TN) sets out the findings and recommendations made in the Financial Sector Assessment Program (FSAP) for the Russian Federation (RF) in the areas of Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT). It summarizes the findings of a targeted review of several aspects of the RF’s progress in addressing vulnerabilities in the financial sector, specifically the banking sector. A full assessment of the AML/CFT framework against the current FATF standard will be conducted by the FATF, Eurasia Group and MONEVYAL, and will be available in 2019.Some authorities have improved their understanding of money laundering and terrorist financing (ML/TF) risks, however the swift finalization of the national risk assessment (NRA) will further advance that understanding and the use of risk-based approach by all concerned agencies and reporting entities.The authorities took measures to prevent the abuse of Russian companies for ML/TF purposes, but more efforts are needed to ensure that timely and accurate beneficial ownership information is available to the authorities.Preventive measures related to politically exposed persons (PEPs) and reporting of suspicious transactions were updated and are largely in line with the FATF standards, however the PEPs definition requires further amendments and the effectiveness of the measures should be enhanced further.The AML/CFT supervision of banks is comprehensive and related sanctions are effective, but further progress could be made to enhance risk-based supervision and AML/CFT tools.